Development of the Australian hospital patient experience question set for parents. Issue 2 (April 2023) - Nelson, Helen J; Pienaar, Catherine; McKenzie, Katie; Williams, Anne M; Swaminathan, Girish; Mӧrelius, Evalotte
ABSTRACT: Background: The Australian Commission on Safety and Quality in Health Care developed the Australian Hospital Patient Experience Question Set to ask adult patients about their experience of inpatient care. This question set was not validated for paediatric care. Aim: To adapt and validate the Australian Hospital Patient Experience Question Set for parents and carers of children who received inpatient care. Methods: Interviews with fourteen parents and carers were conducted. Content analysis was used to revise the question set and to identify experience specific to children and parents. The Question Set was revised, including three new questions to reflect parent experience. Content validity of each new question was assessed. Data was split and construct validity assessed using exploratory and confirmatory factor analysis (n = 1500). Findings: Two main qualitative categories of care included 'parent experience' and 'children being heard'. Emotional support was an integral aspect of parent experience. The revised question set (13-question, one-factor model of good fit) demonstrated construct validity (n = 500: Root Mean Square Error of Approximation = 0.042, Confirmatory Fit Index = 0.997, Tucker Lewis Index = 0.996, Composite reliability = 0.962). Discussion: This study adds empirical support for a common measurement framework for experience of care in children's health services. Parents spoke of the value of having a parent and a child reported survey. The next step is for children to report on their own experience. Conclusion: The revised (parent-reported) question set provides a validated tool which reflects the unique experience of parents and facilitates consistent monitoring and improvement of patient experience in a paediatric inpatient setting.